Comparing Traditional Soil Extraction With Ion Exchange Resin Capsules for Determining Sulfur Bioavailability in Semiarid Low-Fertility Soils. Issue 1 (January 2016) - Buck, Rachel L.; Webb, Bruce L.; Jolley, Von D.; Roundy, Bruce A.; Hopkins, Bryan G.
Abstract : Abstract: Sulfur (S) is an essential plant nutrient found in most soils primarily in the organic matter phase; consequently, predicting bioavailability is difficult. Ion exchange resin capsules provide a viable alternative to soil chemical extraction tests in evaluating the S status of fertilized soils, but their validity in desert ecosystems is not known. Field studies were established on crested wheat stands in both Rush Valley and Skull Valley, Utah. Six rates of S (0, 7, 14, 28, 56, 112 kg S ha −1 ) were broadcast applied. In the first study, resin capsules were removed and replaced, and soil samples were taken every 90 days for 1 year. Resin capsules and conventional soil extractions were both effective in distinguishing among fertilizer rates on most dates, although at the last sampling, only the conventional soil extraction was related to S applied. The second field study used the same fertilizer rates as previously described, but a resin capsule was placed in each plot at 0- to 5-, 5- to 10-, and 10- to 15-cm soil depth. Resin capsules were removed and replaced after 90 days, and final removal occurred 398 days after fertilizer application. Burial depth was not significant because all depths yielded significant correlation to S applied, except the surface depth through the first sampling period. For both field studies, resin capsule correlation to S applied was good, but soil extraction S estimates were slightly better. Overall, resin capsules appear useful for estimating soil S availability in semiarid low-fertility conditions. However, soil moisture should be carefully monitored. Further research is needed to relate resin capsule S to plant uptake.